Professional Training of Future Teachers of Geography in Historical Retrospect - Chubrei, Oleksandra (Pedagogical Discourse, 2019)
The article describes the peculiarities of professional training of future geography teachers in historical retrospect. There have been some discrepancies in scientific views regarding the periodization of the stages of formation and development of professional training of future teachers of geography. It was clarified that the publications of O. Horbatiuk present a retrospective analysis of the processes of formation and development of the Ukrainian higher pedagogical school, which in the light of reforming the education system in Ukraine is of particular relevance. O. Braslavska identifies three periods of formation of national geographical education. I. Shorobura defined four periods of formation and development of school geographical education in the nineteenth and twentieth centuries. The works of L. Melnychuk describe the formation and development of school geographic education in Ukraine in the first half of the twentieth century. O. Timets, analyzing the history of the formation of vocational training for future teachers of geography, proposes a periodization covering four historical periods. In the monograph by Ya. Oliinyk and N Krasnopolska «Geographic Science in Ukraine: Formation and Development» the stage of geographical science is established and four stages of its development are identified. Based on the analyzed approaches to the periodization of the genesis of the education system of Ukraine as a whole and of pedagogical education in particular, it is concluded that certain peculiarities of the national pedagogical education are related, first of all, to the objective laws of socio-political, economic and cultural development of the country, and quantitative changes in society, social requirements, the nature of cultural change, etc. All these factors had a significant impact on the formation of different components of teacher education. Taking as a basis the above stages of formation and development of the system of professional training of future teachers of geography and supplementing them with the results of modern psychological and pedagogical researches, we propose our own periodization of the phenomenon under study. The basis of our periodization is not only changes in the social life of Ukraine, but also the development of geographical education as a system with qualitative shifts in content, approaches to the study of phenomena, teaching methods at different stages of development, caused, above all, by educational reforms.